Italy’s progress towards the objectives of the national action plan to combat antimicrobial resistance - Costanza Vicentini; Stefania di Giacomo; Luca Bresciano; Giulia Fadda; Adriano Grossi; Fortunato D’Ancona; Carla Maria Zotti (PLoS ONE, 2026)
Background Antimicrobial resistance (AMR) represents a major public health threat. Italian AMR rates are among the highest in Europe. The Italian National action plan to combat AMR was launched in 2017 and updated in 2022. To monitor its implementation, the self-assessment tool SPiNCAR (Supporto al Piano nazionale per il contrasto all’antimicrobico resistenza) was developed. Methods We conducted the first national data collection through SPiNCAR in 2023, assessing the level of implementation across Italian regions and autonomous provinces for the year 2022. Regional SPiNCAR scores were correlated with relevant indicators: healthcare-associated infection (HAI) and antimicrobial use prevalence, as well as antibiotic consumption. Results Thirteen regions and autonomous provinces participated. High implementation levels were observed in the SPiNCAR areas of governance, surveillance, HAI prevention and control, and antimicrobial stewardship, while education, stakeholder engagement, and performance assessment showed the lowest scores. Moderate inverse correlations emerged between governance scores and HAI prevalence, and between surveillance/appropriate use scores and antimicrobial use prevalence. A strong inverse correlation was found between performance assessment scores and antimicrobial use prevalence. Conclusions This study provides the first national baseline assessment of the level of implementation of the Italian National action plan to combat AMR. Results suggest SPiNCAR could be a useful tool to monitor AMR policies in decentralized health systems. Findings highlight both achievements and gaps; repeated assessments are necessary to guide targeted interventions and reduce regional inequalities.